2008
DOI: 10.1002/ca.20736
|View full text |Cite
|
Sign up to set email alerts
|

Reverse total shoulder arthroplasty

Abstract: Reverse total shoulder arthroplasty designs have gained popularity over the last few years due to their satisfactory functional results in patients with cuff-tear arthropathy and other difficult reconstructive shoulder problems. These semiconstrained prostheses improve stability and active elevation in the absence of a functional rotator cuff by coupling a spherical glenoid component with a concave humeral component and increasing deltoid tension. Understanding the anatomy of the shoulder is critical in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 40 publications
0
33
0
1
Order By: Relevance
“…The major indication for using RTSA is arthritis associated with massive rotator cuff tears which accounts for approximately 90 % of the cases in different series [2,5,6,8,9,22]. The patient's age is important for the indication, as the implant longevity is not well understood; therefore, most authors do not advocate use of this type of implant for patients under 65 years of age [1,5,9,[23][24][25][26]. The use of reverse arthroplasty changes the Fig.…”
Section: Indicationsmentioning
confidence: 99%
“…The major indication for using RTSA is arthritis associated with massive rotator cuff tears which accounts for approximately 90 % of the cases in different series [2,5,6,8,9,22]. The patient's age is important for the indication, as the implant longevity is not well understood; therefore, most authors do not advocate use of this type of implant for patients under 65 years of age [1,5,9,[23][24][25][26]. The use of reverse arthroplasty changes the Fig.…”
Section: Indicationsmentioning
confidence: 99%
“…In the reverse prosthesis, an opposite trend is observed, with a stability ratio in average 60% higher in the 90° abducted position than in the resting position. This, potentially associated with decoaptation through impingement of the humeral component on the glenoid/scapular neck, 4 may partly explain why the reversed shoulder rather dislocates in the adducted position, 35 while the intact joint is likely to dislocate in the abducted and externally rotated position. 42 The standard configuration (encircled data in Figure 3 with the glenoid in neutral version and the humeral component in the physiologic 20° of retroversion) yielded low intrinsic stability.…”
Section: Discussionmentioning
confidence: 99%
“…7,17 Distortion of the osseous and softtissue anatomy by prior trauma, poor deltoid tensioning, inappropriate ratio between the central depth and the diameter of the concave component, leverage of the humeral component against the glenoid bone and components malpositioning have been identified as possible causes of instability. 4,13,17,23,25,35,40 Revision surgery for correction of instability has been advocated in case of component malpositioning, 23 However until now, no clear and explicit recommendations for adequate component positioning are available. 20 A primary factor in resisting dislocating forces is the geometry (conformity and constraint) of the implant itself, 2,11,32,36 especially in the semi-constrained reverse setting.…”
Section: Introductionmentioning
confidence: 99%
“…Scapular notching is the most common complication observed in 44% to 96% of all the cases. [1][2][3][4][5][6][7][8] Studies have not reported a correlation between scapular notching and the clinical results or implant failure, 2,9) but it has been shown that superior invasion of scapular notching into the inferior screw that supports the glenoid base plate can adversely affect the glenoid component or shoulder function. 1,10) As the pathological effects of scapular notching exacerbates with time, 9,11) it must be treated promptly and its occurrence minimized.…”
Section: Introductionmentioning
confidence: 99%